A case report of primary psammomatous serous adenocarcinoma of the peritoneum. Issue 1 (7th April 2016) - Patil, Purwa R; Bharambe, Bhavana M; Mahure, Aditi H; Kurdukar, Madhumita D; Patil, Amruta A; Deshpande, Kalpana A
Abstract : Extraovarian peritoneal serous papillary carcinoma is an uncommon malignant tumour characterised by peritoneal involvement with ascites, which is similar to ovarian serous papillary carcinoma histologically. Our case involved only the surface and superficial cortex of the ovaries, with peritoneal involvement, as described in the literature.